PENGARUH PEMIKIRAN ISLAM REVOLUSIONER ALI SYARIâATI TERHADAP REVOLUSI IRAN - Nugroho, Anjar (Muhammadiyah University Press, 2014)
The Islamic revolution of Iran happened in 1979 shows as the most realexample of how people power could take over the tyranny era and monarchy systemlasting for 200 years in Iran. Their collective awareness is caused by the source ofreligion awareness (Shia Islam) that has been up dated. Ali Syariâati became thebrightened intellectual actor, that is as the phenomenon of the dictator grinding thepeople in Syah Pahleviâs Government. Syariâati, then, acted as the pioneer of radicalideas about revolution and Islam which taken from Shia teachings as the source, thathave been mixed with the tradition of the third World Revolutionary and Marxism. AliSyariâati succeed developing revolutionary Islam ideology in which, then, becomes thebasis of peopleâs collective awareness opposing the era of Syah Pahleviâs Government.According to Ali Syariâatiâs idea, Islam is a freedom and emancipation ideology. accordingto him this idea of Islam is progressive and revolutionary, sourcing to one system offaith, that is; tauhid. If the tauhid based on Ali Syariâatiâs idea is the unity of God,Human and Environment, so the condition of community having social discrimination,injustice and the arbitrary can be classified as syirk.It is the opposing of tauhid. Theoffer of Syariâatiâs idea and Islam ideology become the bridge or the fourth way of deadlock ideology pre-revolutionary opposition movements. They are Secular-nationalist,Communist-Marxist and Islam Fundamentalism. Finally, this Syariâatiâs ideology leadsImam Khomeini to be accepted as the revolutionary leader.Key Words: iran revolution; Shia, and freedom.Revolusi Islam Iran yang terjadi pada 1979 adalah contoh paling nyata,bagaimana kekuatan massa mampu menumbangkan rezim tiranik sekaligus sistemmonarki yang sudah berumur 200 tahun di Iran. Kesadaran kolektif massa itu disebutsebutbersumber dari kesadaran agama (Islam Syiâah) yang sudah diperbaharui. AliSyariâati muncul menjadi sosok intelektual tercerahkan adalah fenomena kekuasaanrezim Syah Pahlevi yang otoriter dan menindas.Syariâati lalu tampil sebagai peloporgagasan-gagasan radikal tentang Islam dan revolusi yang bersumber dari ajaran Syiâahyang sudah dicangkokkan dengan tradisi revolusioner Dunia Ketiga dan Marxisme.Ali Syariâati berhasil membangun ideologi Islam revolusioner yang kemudian menjadibasis kesadaran kolektif massa menentang kekuasaan rezim Syah. Dalam pemikiranSyariâati, Islam adalah sebuah ideologi emansipasi dan pembebasan.Pandangan IslamAli Syariâati yang progresif dan revolusioner bersumber pada satu sistem keyakinanyaitu tauhÃ®d.Jika tauhÃ®d dalam pandangamanusia dan alam semesta, maka kondisi masyarakat yang penuh diskriminasi sosial,ketidakadilan, dan kesewenang-wenangan dapat dikategorikan sebagai Syirk, lawandari tauhÃ®d. Tawaran pemikiran dan ideologi Islam Syariâati menjadi jembatan ataujalan keempat dari kebuntuan ideologi gerakan oposisi pra-revolusi, yaitu antaranasionalis-sekuler, Marxis-Komunis dan Fundamentalisme Islam.Dan ideologi Syariâatimelapangkan jalan bagi diterimanya Imam Khomeini sebagai pemimpin revolusioner.Kata Kunci: revolusi Iran; syiâah; pembebasann Syariâati adalah kesatuan antara Tuhan,